Cost-Effectiveness of Early Versus Standard Antiretroviral Therapy in HIV-Infected Adults in Haiti - Koenig, Serena P. (Public Library of Science, 2011)
BACKGROUND: In a randomized clinical trial of early versus standard antiretroviral therapy (ART) in HIV-infected adults with a CD4 cell count between 200 and 350 cells/mm(3) in Haiti, early ART decreased mortality by 75%. We assessed the cost-effectiveness of early versus standard ART in this trial. METHODS AND FINDINGS: Trial data included use of ART and other medications, laboratory tests, outpatient visits, radiographic studies, procedures, and hospital services. Medication, laboratory, radiograph, labor, and overhead costs were from the study clinic, and hospital and procedure costs were from local providers. We evaluated cost per year of life saved (YLS), including patient and caregiver costs, with a median of 21 months and maximum of 36 months of follow-up, and with costs and life expectancy discounted at 3% per annum. Between 2005 and 2008, 816 participants were enrolled and followed for a median of 21 months. Mean total costs per patient during the trial were US$1,381 for early ART and US$1,033 for standard ART. After excluding research-related laboratory tests without clinical benefit, costs were US$1,158 (early ART) and US$979 (standard ART). Early ART patients had higher mean costs for ART (US$398 versus US$81) but lower costs for non-ART medications, CD4 cell counts, clinically indicated tests, and radiographs (US$275 versus US$384). The cost-effectiveness ratio after a maximum of 3 years for early versus standard ART was US$3,975/YLS (95% CI US$2,129/YLS–US$9,979/YLS) including research-related tests, and US$2,050/YLS excluding research-related tests (95% CI US$722/YLS–US$5,537/YLS). CONCLUSIONS: Initiating ART in HIV-infected adults with a CD4 cell count between 200 and 350 cells/mm(3) in Haiti, consistent with World Health Organization advice, was cost-effective (US$/YLS <3 times gross domestic product per capita) after a maximum of 3 years, after excluding research-related laboratory tests. TRIAL REGISTRATION: ClinicalTrials.gov NCT00120510 Please see later in the article for the Editors' Summary